2010
DOI: 10.1139/f10-098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper, cadmium, lead, and arsenic in a live diet on juvenile fish growth

Abstract: The effects of diet-borne copper, cadmium, lead, and arsenic on juvenile fish were evaluated using a live diet consisting of the oligochaete Lumbriculus variegatus . In 30 d exposures, no effects were observed on the growth and survival of rainbow trout ( Oncorhynchus mykiss ), fathead minnow ( Pimephales promelas ), and channel catfish ( Ictalurus punctatus ) fed diets contaminated with copper [130–310 µg Cu·(g dm)−1], cadmium [90–540 µg Cd·(g dm)−1], and lead [850–1000 µg Pb·(g dm)−1]. However, rainbow trout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 19 publications
0
44
0
1
Order By: Relevance
“…Hydrospychid caddisflies were targeted for Cu because they have been recommended as an indicator taxa for interpreting metals in tissues of aquatic insects (Rainbow et al, 2012). Hydrospychid caddisflies and two stonefly taxa at different trophic levels were also targeted for As speciation analyses in 2012 because of reports linking dietary exposure of inorganic As to reduced growth of Rainbow Trout (Erickson et al, 2010).…”
Section: Sampling and Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrospychid caddisflies were targeted for Cu because they have been recommended as an indicator taxa for interpreting metals in tissues of aquatic insects (Rainbow et al, 2012). Hydrospychid caddisflies and two stonefly taxa at different trophic levels were also targeted for As speciation analyses in 2012 because of reports linking dietary exposure of inorganic As to reduced growth of Rainbow Trout (Erickson et al, 2010).…”
Section: Sampling and Analysis Methodsmentioning
confidence: 99%
“…Arsenic and Fe have been shown to be strongly correlated in Panther Creek sediments (r >0.9), suggesting sequestration in Fe oxyferrihydroxides in stream sediment (Mok and Wai, 1989;Mebane, 1994;Gray and Eppinger, 2012). Erickson et al (2010), noted that inorganic arsenic in the diet of trout at about 20 mg/kg dry weight (dw) or higher has been correlated with reduced growth, and in their feeding study with live invertebrate diets enriched with arsenic, 26 mg/kg dw or higher arsenic in the diet was directly demonstrated to impair growth in Rainbow Trout. Arsenic residues in Panther Creek invertebrate tissue were slightly above 20 mg/kg dw in some years, although the years with lower condition factors in fish did not match years with elevated arsenic in invertebrate tissues (Figures 2 and 10).…”
Section: Arsenicmentioning
confidence: 99%
“…Chronic exposure to arsenic leads to a number of diseases including cancer of the skin, bladder, kidney and liver; diabetes; cardiovascular and lung diseases (Abernathy et al, 2003; Hughes et al, 2011). In teleosts, exposure to sublethal concentrations of arsenic has been linked to reduced growth, attenuated stress response, and increased oxidative stress (Bears et al, 2006; Eisler, 1988; Erickson et al, 2010; Ventura-Lima et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Erickson et al (2010) reported a significant reduction of growth performance of rainbow trout, Oncorhynchus mykiss, exposed to arsenic. In this study, the ammonia exposure caused a notable decrease in growth performance of S. schlegelii.…”
Section: Discussionmentioning
confidence: 99%